Village Government Supporting Agency Model With School Committee in Supporting Education Funding - Saman, Asrina; Mahmudah, Fitri Nur; Suyatno, Suyatno (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
Funding is crucial for operational implementation in educational institutions. So, other parties that do not conflict with laws and regulations have a significant role to play in becoming supporting agencies in education financing. This study attempts to explore the role of the village government and the school committee in supporting education financing using a case study approach and qualitative research. The research findings contained four components: 1) educational Process effectiveness, 2) financing support, 3) the need for a plan analysis, and 4) stakeholder role urgency. Of the four components, two of them are part of the village government's role, namely the Effectiveness of the Education Process and Financing Support, and two other components, namely the Need for plan analysis and the Urgency of the Role of Stakeholders, are part of the role of the school committee. The conclusion is that the role of the Village Government in supporting education funding is by providing financial support through village meetings, which then gave birth to a program, namely "paying temporary honorary teacher salaries". However, regarding the school committee, which is still not optimal in carrying out its roles and functions, the commitment of the school committee in carrying out its role is not exemplary because the school committee still only follows directions from the school.